The shepherd's granddaughter - Carter, Anne (Groundwood Books / House of Anansi Press, 2008)
Amani longs to be a shepherd like her grandfather, Seedo. Like many Palestinians, her family has grazed sheep above the olive groves of the family homestead for generations, and she has been steeped in Seedo's stories, especially one about a secret meadow called the Firdoos--and the wolf that once showed him the path there